INFLUENCE OF LONG TERM FERTILIZATION ON YIELD AND ACTIVE POOLS OF SOIL ORGANIC CARBON IN RICE - RICE CROPPING SEQUENCE OF ONATTUKARA - G. KAVYASREE; V. MINI (The Journal of Research ANGRAU, 2022)
The effect of long term fertilization on yield and active pools of soil organic carbon under ricerice cropping sequence was studied during 2020-21 in a long term fertilization experiment conducted since 1964 at Onattukara Regional Agricultural Research Station, Kayamkulam, Kerala. The results indicated that the application of FYM along with NPK fertilizers(80 kg N ha-1, 20 kg as FYM and 60 kg as A.S. + 40 kg P2O5 ha-1 as Rajphos + 40 kg K2O ha-1) as MOP resulted in significant increase in rice yield. Soil organic carbon, soil microbial biomass carbon, nitrogen, and phosphorus, water soluble carbon, water soluble carbohydrates and dehydrogenase activity were the highest under treatment receiving combined application of FYM and NPK fertilizers. These fractions contribute to the active pool of soil organic carbon and can be identified as an indicator of soil quality. Present study thus provided an insight on how management practices affect crop yield and active pools of carbon.